Kajian Literatur : Harapan Pasien Terhadap Layanan Konseling di Apotek - Auliyana, Iftitah Putri; Setiadi, Antonius Adji Prayitno; Wibowo, Yosi Irawati; Gondokesumo, Marisca Evalina (Universitas Malahayati, 2025)
ABSTRACT Drug Counseling is an interactive process between pharmacists and patients/families to increase knowledge, understanding, awareness and compliance so that changes in behavior in drug use occur and resolve problems faced by the patients. This literature review aims to look at the expectations that affect patient or consumer involvement in counseling at the pharmacy. The articles in this literature review use one database, namely Pubmed. Search results using the keyword combination (community pharmacy) AND (counseling OR communication OR patient counseling factors OR patient participation) AND (patient expectations) yielded 408 articles that met the inclusion criteria in this study are 13 articles. The results of the literature review show that the expectations that affects the patient or consumer involvement in counseling at the pharmacy are providing good information with appropriate communication skills, the layout of the pharmacy and the relationship between the pharmacist or pharmacist staff and the patient being good, friendly and polite. Keywords: Community Pharmacy, Counseling, Patient Counseling, Patient Expectations, Patient Participation. ABSTRACT Konseling Obat merupakan proses interaktif antara apoteker dengan pasien/keluarga untuk meningkatkan pengetahuan, pemahaman, kesadaran dan kepatuhan sehingga terjadi perubahan perilaku dalam penggunaan obat dan menyelesaikan masalah yang dihadapi pasien. Kajian literatur ini bertujuan untuk melihat harapan yang mempengaruhi keterlibatan pasien atau konsumen dalam konseling di Apotek. Artikel pada kajian literatur ini menggunakan satu database yaitu Pubmed. Hasil pencarian dengan kombinasi kata kunci (community pharmacy) AND (counseling OR communication OR patient counseling factors OR patient participation) AND (patient expectations) menghasilkan 408 artikel yang memenuhi kriteria inklusi dalam kajian ini yaitu sebanyak 13 artikel. Hasil kajian literatur menunjukkan bahwa harapan yang mempengaruhi keterlibatan pasien atau konsumen dalam konseling di Apotek yaitu pemberian informasi yang baik dengan keterampilan komunikasi yang tepat, tata letak apotek dan hubungan apoteker atau staf apoteker dengan pasien baik, ramah dan sopan. Kata Kunci: Farmasi Komunitas, Konseling, Konseling Pasien, Harapan Pasien, Partisipasi Pasien